Places and functions of civil procedural legal relations in the mecanism of civil processing regulation - Didenkо, L. V.; Abroskin, V. V.; Andreichenko, S. S.; Bondar, V. V.; Chebotareva, G. V. (Lviv-Toruń : Liha-Pres, 2019)
The article deals with the analysis of the place and functions of civil procedural relations. The author emphasizes that in the mechanism of civil procedural regulation can undergo significant changes both from the point of view of the organization (for example, by expanding the scope of civil jurisdiction), and from the point of view of changing the scope of rights and obligations of subjects of civil procedural regulation in the process of improvement relevant legal institutions. The author examines the place and functions of civil procedural relations in the mechanism of civil procedural regulation. Many of the studies we analyzed were carried out many years ago, and the development of public relations and legislation in our country is permanent, which makes the actual implementation of this research. The author analyzes the main feature of the functions and the general theoretical functions of civil procedural relations in the mechanism of civil procedural regulation. The author emphasizes the peculiarities of civil procedural relations in the mechanism of civil procedural regulation.
Didenko L. V. Places and functions of civil procedural legal relations in the mechanism of civil processing regulation. Theoretical and practical problems of the legal regulation of social relations : collective monograph / V. V. Abroskin, S. S. Andreichenko, V. V. Bondar, G. V. Chebotareva, etc. Lviv-Toruń : Liha-Pres, 2019. - P. 93-109.
Keywords: civil procedural regulation; structural elements of the mechanism of civil procedural regulation; functions of civil procedural legal relations